Module Development in Arts and Culture Subjects at SMPN 1 Batang Anai - Syatifa Marta; Mulyadi Mulyadi (Indonesian Journal on Education (IJoEd), 2025)
This research aims to develop and validate a sculpture art teaching module for cultural arts subjects in grade IX at SMPN 1 Batang Anai. Initial observations showed that cultural arts learning still uses conventional learning resources in the form of textbooks and worksheets with monotonous displays that are less motivating for students. This research uses the ADDIE development model (Analyze, Design, Development, Implementation, Evaluation) which is limited to the Development stage. The Analyze stage was conducted through questionnaires to 5 validators and field observations that identified learning problems including limited media, limited learning resources, and low student reading interest. The Design stage designed modules using PowerPoint and Construct 2 with Adobe Photoshop, Comic Sans MS 14 pt font, dominant cream color, front page structure, navigation menu, and evaluation instruments. The Development stage produced a teaching module product with attractive design, motivational cartoon images, and navigation that facilitates access to learning activities 1-4. Material expert validation showed Cronbach's Alpha reliability of 0.931 with 100.0% valid criteria, while design expert validation showed Cronbach's Alpha reliability of 0.875 with 100.0% valid criteria. The research results show that the developed sculpture art teaching module is suitable for use in cultural arts learning based on the assessment of material and design expert validators.